H. pylori eradication therapy for patients receiving nonsteroid antiinflammatory drugs - V. T. Ivashkin; T. L. Lapina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate value of H. pylori eradication therapy in patients for prophylaxis and treatment of nonsteroid antiinflammatory drugs (NSAID)- induced gastropathies.Key points. NSAID and H. pylori act as independent risk factors of ulcer development. Eradication therapy is the major way of prevention of gastroduodenal ulcer and its complications, especially if prophylaxis is carried out prior to onset of NSAID treatment. At long-term application of NSAID the preventive effect of H. pylori eradication is less pronounced. Low doses or special aspirin preparations can not only cause erosions and ulcers, but also result in development of gastro-intestinal bleedings. Well-timed eradication therapy in patients receiving aspirin can decrease risk of ulcer bleeding even without maintenance treatment by proton pump inhibitors (PPI). Diagnostics H. pylori with prescription of antihelicobacter therapy at positive result should be provided in all patients receiving aspirin, with peptic ulcer in past history. Pantoprazole should be preferred at complex treatment of these patients to decrease adverse effects due to drug interaction.Conclusion. Successful and well-timed combination of eradication treatment and standalone PPI therapy is the important prerequisite in avoidance of dangerous gastro-intestinal complications at intake of NSAID and aspirin.